Pembelajaran “Rasenda” untuk Meningkatkan Keaktifan dan Hasil Belajar IPA di MTs Negeri 1 Bantul - Budiati, Asih (Jurnal Pendidikan Madrasah, 2024)
This study aims to improve student activeness and learning outcomes in science subjects. This research is a best practice with the subject of research being class IX-E students at MTs Negeri 1 Bantul. This study tries to describe Rasenda's learning method (Summarizing, Percentage, and Deepening of Material). Data were collected through observation, documentation, and learning outcomes tests. Data analysis uses qualitative analysis techniques. The results showed that the Rasenda model had a positive effect on the activeness and learning outcomes of science. This is shown by the increase in student activity during learning at all stages of Rasenda by 60.8% in material I and increased to 80.7% at the end of material II. Similarly, student learning outcomes are the highest score of 78 in material I to 87 in material II, the lowest score of 60 in material I to 67 in material II, and the average score from 65.56 in material I to 80.20 in material II. The Rasenda method can improve activeness and science learning outcomes in MTs Negeri 1 Bantul for the 2023-2024 academic year.